Competing currencies in the laboratory - Janet Hua Jiang; Cathy Zhang (Bank of Canada, 2017)
We investigate competition between two intrinsically worthless currencies as a result of decentralized interactions between human subjects. We design a laboratory experiment based on a simple two-country, two-currency search model to study factors that affect circulation patterns and equilibrium selection. Experimental results indicate foreign currency acceptance rates decrease with relative country size but are not significantly affected by the degree of integration. The laboratory economies tend to converge to a unified currency regime where both currencies circulate at home and abroad, even if other regimes are theoretical possibilities. Introducing government transaction policies biased towards domestic currency significantly reduces the acceptability of foreign currency. These findings suggest government policies can serve as a coordination device when multiple currencies are available.
Keywords: C92; D83; E40; 330; Central bank research; Digital currencies